TEACHING PRACTICE: OPPORTUNITY TO THE POST GRADUATION STUDENT - Patrícia Maria Marcon; Maria de Fátima Mantovani; Marineli Joaquim Meier (Universidade Federal do Paraná, 2005)
This article presents an experience account related to the subject Teaching Practice , which belongs to the compulsory subjects of the Master course at the post graduation program in Nursing of the Federal University of Paraná. The subject presents the opportunity to teach for the graduation course, at the same institution, in the discipline of Semiotechnique II. Believing that this is a significant experience to all the involved parts, the article objectifies to describe the main moments lived during the teaching practice. Thus, this study was structured to present: the contextualized postgraduation program and its disciplines; the graduation subject, the way to prepare the classes, the expectations and assessment of the graduation students as well as those of the ostgraduation student (as a teacher). The teaching practice was considered not only a valuable opportunity, but also a necessary one to postgraduation students. It was concluded that such an activity must be stimulated in other postgraduation courses.